2018
DOI: 10.1371/journal.pone.0209075
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temporal aggregation level in social network monitoring

Abstract: Social networks have become ubiquitous in modern society, which makes social network monitoring a research area of significant practical importance. Social network data consist of social interactions between pairs of individuals that are temporally aggregated over a certain interval of time, and the level of such temporal aggregation can have substantial impact on social network monitoring. There have been several studies on the effect of temporal aggregation in the process monitoring literature, but no studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…In some cases, performance is better in count settings, but not in others. 13 We make note the design of S * method is to detect if a change occurred rather than to identify the time-points said change occurred in Priebe et al 14 and Zhao et al 12 That is, when monitoring the scan statistic, the method is expected to signal at best only a few times if any anomaly occurred. In AUC results reported in Tables A1-A4 in Appendix A3, the detection ability is mainly best for M − t and M + t methods in DLSM settings while the W t method does detect best in DDCSBM settings.…”
Section: Performance Evaluation With Anomalies In Edge Probabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, performance is better in count settings, but not in others. 13 We make note the design of S * method is to detect if a change occurred rather than to identify the time-points said change occurred in Priebe et al 14 and Zhao et al 12 That is, when monitoring the scan statistic, the method is expected to signal at best only a few times if any anomaly occurred. In AUC results reported in Tables A1-A4 in Appendix A3, the detection ability is mainly best for M − t and M + t methods in DLSM settings while the W t method does detect best in DDCSBM settings.…”
Section: Performance Evaluation With Anomalies In Edge Probabilitiesmentioning
confidence: 99%
“…Similarly, several papers contain studies of network monitoring under specific parametric modeling frameworks. [10][11][12][13] However, such monitoring methods work under the assumption of a specific network model and cannot be extended to the general task of network monitoring without model assumptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al studied the properties of the scan method of Priebe et al under the assumption of the Erdős and Rényi model. In addition, we have studied monitoring under the assumption of the degree‐corrected stochastic block model (see the works of Wilson et al, Zhao et al, and Yu et al). Zhao et al showed that there can be a substantial loss of information in using unweighted graphs when weighted graphs are available.…”
Section: Social Network Surveillancementioning
confidence: 99%
“…It has been pointed out that the frequency with which observations are sampled deterministically influences the speed with which anomalies are identified . A practical reality is that the sampling frequency is sometimes fixed by the incumbent data acquisition scheme.…”
mentioning
confidence: 99%